Kerentanan Sistem Pertanian Akibat Eksternalitas Industri Energi : Studi Kasus Proyek Geothermal di Desa Batukuwung Padarincang, Banten (International Forum of Researchers and Lecturers, 2025)
The Geothermal Power Plant (PLTP) project in Batukuwung Village, Padarincang District, Serang Regency, has raised concerns among the community about the threat of environmental damage and disruption of the sustainability of the local agricultural system. So far, the community has depended on traditional agriculture that is closely tied to local social, cultural, and ecological values. PLTP projects, which are framed as part of the clean energy transition, actually create tensions between development and environmental conservation. This research aims to examine the social and ecological impact of the PLTP project on the lives of the village community. The method used is a qualitative approach with case studies. Data were collected through purposive sampling techniques for in-depth interviews with affected residents, community leaders, and environmental activists, as well as analysis of online media content and policy documents. The results of the study show that the presence of the project has created ecological and social vulnerability. Disruption to access to clean water, degradation of soil quality, and disruption of agricultural ecosystems are serious threats. In addition, the space for public participation in the project-related decision-making process is very limited, thus triggering resistance and horizontal conflicts. These findings show that the clean energy narrative does not always align with the reality on the ground. Therefore, it is important to consider the principles of ecological justice and the sovereignty of local communities in any energy development policy. This study recommends participatory dialogue and a thorough environmental evaluation before the project proceeds, so that development does not compromise the right of life of local communities and the ecological sustainability of the region. The active involvement of citizens as subjects, not objects of development, is the key to creating sustainable and equitable solutions for all affected parties.